2012
DOI: 10.1158/0008-5472.can-12-0028
|View full text |Cite
|
Sign up to set email alerts
|

Acyclic Retinoid Targets Platelet-Derived Growth Factor Signaling in the Prevention of Hepatic Fibrosis and Hepatocellular Carcinoma Development

Abstract: Hepatocellular carcinoma (HCC) often develops in association with liver cirrhosis, and its high recurrence rate leads to poor patient prognosis. Although recent evidence suggests that peretinoin, a member of the acyclic retinoid family, may be an effective chemopreventive drug for HCC, published data about its effects on hepatic mesenchymal cells, such as stellate cells and endothelial cells, remain limited. Using a mouse model in which platelet-derived growth factor (PDGF)-C is overexpressed (Pdgf-c Tg), resu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 41 publications
1
52
0
Order By: Relevance
“…This is reasonable as we previously showed enhanced inflammatory response and inhibited serum levels of TNFa and expression levels of TNFa, IL6, and IL1b mRNA in the liver of db/db mice treated with ACR compared with those treated with DEN alone (20). Furthermore, in a plateletderived growth factor-overexpressed mouse model, genomewide expression profile analysis revealed that the repressive effect of ACR on the development of hepatic fibrosis and tumors was related with inflammatory signaling pathways such as "MIF signaling" and "IL6 signaling" (44).…”
Section: Discussionmentioning
confidence: 98%
“…This is reasonable as we previously showed enhanced inflammatory response and inhibited serum levels of TNFa and expression levels of TNFa, IL6, and IL1b mRNA in the liver of db/db mice treated with ACR compared with those treated with DEN alone (20). Furthermore, in a plateletderived growth factor-overexpressed mouse model, genomewide expression profile analysis revealed that the repressive effect of ACR on the development of hepatic fibrosis and tumors was related with inflammatory signaling pathways such as "MIF signaling" and "IL6 signaling" (44).…”
Section: Discussionmentioning
confidence: 98%
“…The spectrum of feasible therapies include cyclooxygenase inhibitors, proteaseactivated receptor inhibitors, and glycoprotein IIb/IIIa (GPIIb/IIIa) inhibitors. (6,12,(34)(35)(36) HCC patients with mild thrombocytopenia are likely better candidates until more scientific data on the safety of those therapies accumulate because such patients can have less bleeding diathesis and greater metastasis risk. In addition, the stable late posttransplant phase might provide another time window for targeting the latent metastasis with less concern about bleeding complications or graft regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…HSC were isolated from C57BL/6J mice by pronase-collagenase liver digestion as reported previously [34]. …”
Section: Methodsmentioning
confidence: 99%
“…Gene expression profiling of mouse liver was performed using a GeneChip Mouse Gene 1.0 ST Array (Affymetrix, Santa Clara, CA) [34]. Liver tissue from mice fed the basal, Ath+HF, or Ath+HF diet containing 3% BCAA for 30 or 60 weeks was obtained.…”
Section: Methodsmentioning
confidence: 99%